THE IMPACT OF COMMUNICATION ON LEADERSHIP: A SIGNIFICANT REVIEW - Rozaimi Jaafar; Wan Marfazila Wan Mahmud; Mohd Fakrul Hafiz Mohd Hanafi; Widad Ma, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Leadership is vital for organizational growth, necessitating examination of core competencies like communication enabling effective leadership especially in turbulent times. This review consolidates research on linkages between leadership communication and emergent leadership outcomes. While predominant focus remains leader-centric, literature reveals complex bidirectional communication flows across hierarchical levels influencing leadership effectiveness and acceptance. However, consolidated clarity regarding distinguishing facets of communication fundamental for impactful leadership remains lacking. This significant review synthesizes multi-level research connecting communication behaviors and processes with leadership emergence and performance spanning interpersonal, team and organizational contexts via conceptual analysis. A framework integrating competencies characterizing distinguished leader-communicators is also put forth based on evidence aggregated. Analysis points to key aspects ranging from conveying cultural empathy to elevating collective identity through inclusive discourse that distinguished leadership communication fundamentally binds leadership vision to contextual interactions driving performance. Findings also critically highlight need for added communication dimensions encompassing restorative justice where adversity erodes leader legitimacy. This seminal review definitively puts forth communication as the core binding element flowing through formal and informal leadership development conduits that ultimately nourishes organizational resilience fit to navigate unprecedented turbulence. The integrated framework crystallizes distinguished communication-based leadership competencies redressing complex sociotechnical mechanisms that can unambiguously advance scholarship and practice on optimizing human centered, ethical and digitally-enabled leader messaging crucial for collective advancement.